Germalus species of the Malagasy region (Heteroptera: Lygaeoidea: Geocoridae) - Kóbor, P.; Kondorosy, E. (Zootaxa, 2016)
Malagasy species of the genus Germalus Stål, 1862 were reviewed based on material of different European museums. Comments on the description of Germalus kinbergi (Stål, 1859) are given with new distribution data on Réunion. Two new species, Germalus banari sp. nov. and Germalus benyovszkyi sp. nov. are described.